The Effect of Construal Level And Spatial Distance in Tourism Destination Advertising on Destination Image And Visit Intention - Rinaldy, Fahmi Ihza; Tumpal, Daniel (Eduvest - Journal of Universal Studies, 2025)
This study examines the destination image differences travel destination advertisements based on the construal level and spatial distance strategies using the Analysis of Variance (ANOVA) test. This study also tested the effect of destination image towards visit intention using the Macro PROCESS with the SPSS software. This research used a factorial design of 2 construal level (high vs low) x 2 spatial distance (far vs near) involving 120 student participants. Before doing the main test, in this study, a manipulation check was made to ensure that the participants understood the scenario and stimuli created by the researcher. The measured variable consisted of destination image (5 indicators), and visit intention (5 indicators). All of the measures used 5 points Likert scale. In this study, using the ANOVA’s main effect, different construal level and spatial distance conditions resulted in significant differences in destination image. It was also found that the combination between construal level and spatial distance produced a significant interaction effect difference in destination image. This study also proved that destination image had a positive effect on reservation intention.